Multi-Hazard Assessment of Bridges in Case of Hazard Chain: State of Play and Application to Vehicle-Pier Collision Followed by Fire - Petrini, Francesco; Gkoumas, Konstantinos; Rossi, Claudio; Bontempi, Franco (Frontiers in Built Environment, 2020)
This study focuses on multi-hazard analysis for bridges, following a two-tier approach. First, it identifies relevant open issues and recent literature developments in the field, presenting data in a meaningful manner, with specific focus on the issues related with the analysis of hazard chain scenario treated as low probability–high consequence events. Second, it describes a practically useful and sufficiently generic approach for efficient computational investigation of hazard chain scenarios in highway bridges. Following that, the applicability of the approach is exemplified in an appealing and commonly encountered in real-life hazard chain scenario, in which a multilevel modeling strategy is adopted to assess the structural response under hazard chain scenarios of a highway viaduct. Among the considered scenarios is the impact of a heavy vehicle (tank truck) on the bridge pier, and the fire spread following the collision due to the presence of inflammable materials. The bridge structure is a typical 189-m-long multi-span composite highway viaduct. The impact is modeled with a non-linear transient dynamic analysis that accounts the inertial effect of the global structure, while the fire modeling is performed with non-linear quasi static dynamic analysis focusing on local behavior with a substructured model. Then different impact and fire scenarios are considered, including different impact velocities of the truck.